PERAN LEMBAGA DAKWAH KAMPUS DALAM MEMBENTUK SIKAP KEBERAGAMAAN MAHASISWA UIN ALAUDDIN MAKASSAR - Muhaemin Latif; Syahru Ramadhan (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2022)
This article discusses the role of the al-Jami' Campus Da'wah Institute (LDK) in shaping the religious understanding of UIN Alauddin Makassar (UINAM) students. The type of research used is qualitative by taking case studies on students of UIN Alauddin Makassar. In collecting data, researchers conducted interviews with several LDK student figures and observed various activities carried out by LDK. The results showed that LDK al-Jami' contributed greatly in increasing the literacy of the Qur'an among UINAM students, especially students from general faculties. LDK even teaches students to pray on time and invites students to follow the sunnahs of the Prophet Muhammad. However, the religious spirit that is close-minded has become an important character for elements of the LDK management which in turn has colored the religious character of students. In other words, the religious nature of exclusivism is more dominant than the spirit of inclusiveness in religion. Their motto is to return to classical traditions and to replicate the romance of the progress and glories of Islam in the past.